Modelling the degradation of vibration characteristics of reinforced concrete beams due to flexural damage - Hamad, W.I.; Owen, J.S.; Hussein, M.F.M. (Wiley, 2015)
This paper presents an improved crack model incorporating non-linearity of flexural damage in concrete to reproduce changes in vibration properties of cracked reinforced concrete beams. A reinforced concrete beam model with multiple-distributed flexural cracks is developed, in which the cracked regions are modelled using the fictitious crack approach and the undamaged parts are treated in a linear-elastic manner. The model is subject to incremental static four-point bending, and its dynamic behaviour is examined using different sinusoidal excitations including swept sine and harmonic signals. From the swept sine excitations, the model simulates changes in resonant frequency with increasing damage. The harmonic excitations are utilised to investigate changes in modal stiffness extracted from the restoring force surfaces, and changes in the level of non-linearity are deduced from the appearance of super-harmonics in the frequency domain. The simulation results are compared with experimental data of reinforced concrete beams subject to incremental static four-point bending. The comparisons revealed that the proposed crack model is able to quantitatively predict changes in vibration characteristics of cracked reinforced concrete beams. Changes are sensitive to support stiffness, where the sensitivity increases with stiffer support conditions. Changes in the level of non-linearity with damage are not suitable for damage detection in reinforced concrete structures because they do not follow a monotonic trend.